Traveling Wave Resonance and Simplified Analysis Method for Long-Span Symmetrical Cable-Stayed Bridges under Seismic Traveling Wave Excitation - Zhong-ye Tian; Meng-lin Lou (Shock and Vibration)
The seismic responses of a long-span cable-stayed bridge under uniform excitation and traveling wave excitation in the longitudinal direction are, respectively, computed. The numerical results show that the bridge’s peak seismic responses vary significantly as the apparent wave velocity decreases. Therefore, the traveling wave effect must be considered in the seismic design of long-span bridges. The bridge’s peak seismic responses do not vary monotonously with the apparent wave velocity due to the traveling wave resonance. A new traveling wave excitation method that can simplify the multisupport excitation process into a two-support excitation process is developed.